Characterization of cast iron scrap chips toward β-FeSi2 thermoelectric materials - Nor Hairin, Assayidatul Laila; Nanko, Makoto (2015, 2014)
The upgrade recycling process of cast-iron scrap chips toward β-FeSi2 is regarded as an eco-friendly and cost-effective production process. It is useful for reducing the material cost in fabricating β-FeSi2 by utilizing the waste that is obtained from the manufacturing process of cast-iron components. In this research, β-FeSi2 was successfully obtained from cast iron bscrap chips and showed good thermoelectric performance in Seebeck coefficient and electrical conductivity which is around 70% to almost 100% compared to β-FeSi2 that was prepared from pure Fe and other publications. The thermoelectric power factor was achieved 90% performance compared to other literatures and β-FeSi2 prepared from pure Fe.